STATIONARY CYCLING DOSAGE FOR PAIN REDUCTION IN OLDER ADULTS WITH KNEE OSTEOARTHRITIS: A SYSTEMATIC REVIEW - Bình Minh, Trần; Quốc Tân, Trương (Journal of Health and Aging, 2026)
This systematic review aimed to identify an effective stationary cycling dosage for pain reduction in adults aged 60 years and older with knee osteoarthritis. The review was conducted according to PRISMA 2020 guidelines, searching PubMed, the Cochrane Library, and PEDro for randomized controlled trials reporting the dosage of stationary cycling interventions. The primary outcome was pain reduction, assessed using standardized scales such as KOOS, WOMAC, and AIMS2. Five studies involving 377 participants were included in the analysis. All 5 studies reported statistically significant pain reduction compared with baseline or control groups. The synthesized intervention dosage comprised a total duration of 8–24 weeks, a frequency of 3–7 sessions per week, a session length of 25–60 minutes, and an intensity ranging from 40–85% of maximum heart rate or 60–110 pedal revolutions per minute. No adverse events relating to the interventions were reported. However, all included studies were judged to be at high risk of bias, primarily due to the inability to blind participants and the use of self-reported scales. Stationary cycling is an effective intervention for pain reduction in older adults with knee osteoarthritis, but the application of training dose should be interpreted cautiously and individualized.